2015
DOI: 10.1097/meg.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

The impact of amalgam dental fillings on the frequency of Helicobacter pylori infection and H. pylori eradication rates in patients treated with concomitant, quadruple, and levofloxacin-based therapies

Abstract: This is the first study to show a lower frequency of H. pylori colonization in patients with amalgam fillings than without and that H. pylori eradication rates are lower in patients with amalgam fillings compared to those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Epidemiological studies have indicated that the prevalence of Helicobacter pylori ( H. pylori ) infection has an incidence of 20–50% in developed countries and 40–60% in China 1 , 2 . H. pylori plays a causative role in many diseases, including gastritis, peptic ulcers, gastric mucosa-associated lymphoid tissue (MALT) lymphoma and gastric cancer 3 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have indicated that the prevalence of Helicobacter pylori ( H. pylori ) infection has an incidence of 20–50% in developed countries and 40–60% in China 1 , 2 . H. pylori plays a causative role in many diseases, including gastritis, peptic ulcers, gastric mucosa-associated lymphoid tissue (MALT) lymphoma and gastric cancer 3 8 .…”
Section: Introductionmentioning
confidence: 99%
“…elicobacter pylori is a common infectious agent worldwide with a prevalence of 20-50% in developed countries and 80% in developing countries [1]. This gram-negative and microaerophilic bacterium colonizes the gastric mucosa and duodenum and causes chronic gastritis as well as diseases such as gastric adenocarcinoma, MALT lymphoma, gastric & duodenal ulcers [2][3][4].…”
mentioning
confidence: 99%